Three-dimensional turbo spin-echo sequence versus conventional two-dimensional turbo spin-echo sequences in the evaluation of lumbar intervertebral discs - Kızılgöz, Volkan; Sivrioğlu, Ali Kemal; Aydın, Hasan; Karayol, Sunay Sibel; Yıldırım, Can Hakan; Menderes, Utku (The European Research Journal, 2018)
Objective: The aim of this study was to evaluate the efficacy of a three-dimensional (3D) turbo spin-echo (TSE) sequence for determining lumbar disc protrusions, and to compare the findings with those of conventional two-dimensional (2D) TSE sequences and reveal the interobserver and intermethod agreements of both sequences. Methods: A total of 127 discs from 84 patients were evaluated by three radiologists. Conventional 2D TSE images and 3D TSE images were independently interpreted with regard to disc pathology and herniation zones and were scored for the degree of spinal stenosis and lumbar neural foraminal stenosis by the three reviewers. To evaluate the lumbar discs, areas of protrusion or extrusion were classified. Interobserver and intermethod reliabilities were calculated using Krippendorff’s alpha (Kα) test.Results: Lumbar disc pathology identification was similar between the 2D TSE and 3D TSE sequences. Interobserver agreements were better for 3D TSE than 2D TSE in the evaluation of disc hernias (Kα ratio; 0.965 vs. 0.944), herniation zones (Kα ratio; 0.894 vs. 0.847), and foraminal narrowing (Kα ratio; 0.965 vs. 0.924). Both 2D and 3D TSE had 100% sensitivity for disc pathologies and spinal stenosis, 81% sensitivity for herniation zones, and 92.5% sensitivity for foraminal stenosis in only operated patients.Conclusions: The 3D TSE sequence was comparable to conventional magnetic resonance imaging (MRI) sequences in the evaluation of lumbar disc herniation. This approach can be used in radiology departments either alone or combined with routine MRI for lumbar disc hernias as a diagnostic sequence and an approach to overcome problems.